2021
DOI: 10.1007/s11747-021-00785-z
|View full text |Cite
|
Sign up to set email alerts
|

How does consumer engagement evolve when brands post across multiple social media?

Abstract: Brands allocate their social media advertising across multiple platforms such as Facebook, Twitter, Instagram, and YouTube. Because consumers use multiple social media, brand communications on one platform could generate engagement within the same platform (direct effects) and potentially impact engagement with the brand on the other platforms (spillover effects). Additionally, past engagement with a post on a platform could sustain into the future, thereby improving the longevity of posts (carryover effects).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 69 publications
1
37
0
1
Order By: Relevance
“…Also, it was found that most works confine their scope of investigation to just one social media platform. The literature lacks a comparative study of how post popularity pans out for the same set of brands on multiple platforms [27]. Therefore, there is limited understanding on the type of content strategy that works well on one platform but fails on another.…”
Section: ) Vividnessmentioning
confidence: 99%
“…Also, it was found that most works confine their scope of investigation to just one social media platform. The literature lacks a comparative study of how post popularity pans out for the same set of brands on multiple platforms [27]. Therefore, there is limited understanding on the type of content strategy that works well on one platform but fails on another.…”
Section: ) Vividnessmentioning
confidence: 99%
“…Regarding the operationalized aspects of digital customer engagement, digital customer engagement is regarded as a continuum of brand-related activities from high to low, exhibiting different levels (Muntinga et al, 2011;Schivinski et al, 2016). Existing research confirms the impact of brand observable social media behaviors on digital customer engagement and that metrics such as likes, comments and shares can represent different levels of engagement (Ji et al, 2019;McShane et al, 2021;Shahbaznezhad et al, 2021;Unnava and Aravindakshan, 2021). For example, Thompson and Brouthers (2021) divide digital customer engagement into share engagement behavior and click engagement behavior, arguing that the two have completely different characteristics.…”
Section: Literature Review and Research Hypotheses Digital Customer Engagementmentioning
confidence: 84%
“…In recent years, many scholars ( Pezzuti et al, 2021 ; Sheng et al, 2021 ; Unnava and Aravindakshan, 2021 ) have generally acknowledged the key role of social media in brand development and emphasized the positive impact of brand engagement behaviors on digital customer engagement. We collected a dataset from the social media platform Weibo.…”
Section: Methodsmentioning
confidence: 99%
“…Instagram posts have longer “enduring effects” (i.e. engagement after the initial posting) than Twitter and Facebook posts (Unnava and Aravindakshan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%